Studies on aggregation behavior in mixed system of single-chained anionic surfactant with single-chained nonionic surfactant in aqueous solution - Mohd Hafiz, Ali (Universiti Malaysia Sarawak, UNIMAS, 2009)
The investigation of mixed surfactants system, mixture of anionic with nonionic surfactants and single surfactants systems, mixture of anionic or nonionic surfactant was investigated using UV/VIS Spectrophotometer to determine the critical micelle concentration, cmc. Mixed surfactants systems studied were mixture of SDS-Triton X-100 and SDS-Brij 35 surfactant solution. While single surfactant systems were SDS, Triton X-100 and Brij 35 surfactant solutions. The determination of cmc that gave aggregations of pyrene between surfactants was characterized. Above cmc, pyrene concentration increased linearly with total surfactant concentration for both mixed and single surfactants system. Mixed surfactant system gave higher cmc than pure surfactant system. The cmc for pure surfactants system gave the following order SDS> Triton X-100 > Brij 35.